2018
DOI: 10.1039/c7sc04688j
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of singlet fission and electron injection in self-assembled acene monolayers on titanium dioxide

Abstract: Electron injection competes with singlet fission in disordered monolayers of tetracene and pentacene-based dyes on mesoporous TiO2 photoelectrodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(76 citation statements)
references
References 70 publications
5
71
0
Order By: Relevance
“…6). The 900 nm feature is consistent with previously-reported cation absorption peak of triisopropylsilylethynyl tetracene carboxylic acid (TIPS-TCA) at~930 nm 46 . Moreover, its formation kinetics is consistent with the decay of the XB within 50 ps.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…6). The 900 nm feature is consistent with previously-reported cation absorption peak of triisopropylsilylethynyl tetracene carboxylic acid (TIPS-TCA) at~930 nm 46 . Moreover, its formation kinetics is consistent with the decay of the XB within 50 ps.…”
Section: Resultssupporting
confidence: 90%
“…The difference spectra are dominated by the XB feature of NCs which exhibits a faster recovery than free NCs. At very long delay times (~30 μs), photoinduced absorption features corresponding to the triplets of tetracene ( 3 TCA*) 28,46 are clearly detected, confirming triplet sensitization or TET from NCs to TCA. However, detailed kinetic analysis is required to uncover the interplay between TET, FRET, hole transfer and hole trapping.…”
Section: Resultsmentioning
confidence: 80%
“…The energetic offset and broadening between the two spectra has previously been observed in other strongly-coupled acene thin lms and underscores the strong coupling that perturbs even fairly localized triplet states. 26,27 There are no triplet features in the sensitized triplet spectrum in the near-IR, which affirms the assignment of observed long-lived bands to the (TT) state in the directly excited lm.…”
Section: Transient Absorption Spectroscopysupporting
confidence: 81%
“…As a consequence, significant contributions from open-shell resonances in the ground state are frequently observed 16 . Keywords that highlight acene-type PAHs with zig-zag periphery range from singlet fission 17 21 , auspicious charge carrier mobilities 22 , 23 , to amplified spontaneous emission 24 , and enlarge the interest in PAHs by the fields of spintronics and molecular magnetism 25 - 27 . Recently, various research groups reported on substituted angularly fused-tetracenes 28 32 , which overcome the low stability of linear acenes, by increasing the intrinsic number of Clar’s-sextets 33 .…”
Section: Introductionmentioning
confidence: 99%